2014
DOI: 10.3384/ecp14096235
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Integration Platform for FMI Co-Simulation and Heterogeneous Simulations of Cyber-Physical Systems

Abstract: Virtual evaluation of complex Cyber-Physical Systems (CPS) [1] with a number of tightly integrated domains such as physical, mechanical, electrical, thermal, cyber, etc. demand the use of heterogeneous simulation environments. Our previous effort with C2 Wind Tunnel (C2WT) [2] [3] attempted to solve the challenges of evaluating these complex systems as-a-whole, by integrating multiple simulation platforms with varying semantics and integrating and managing different simulation models and their interactions. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 20 publications
(31 reference statements)
0
41
0
1
Order By: Relevance
“…After the introduction of FMI, several authors have shown how to use it in modular simulations. A recent example is Neema et al (2014), who used FMI for component models which where integrated using HighLevel Architecture (HLA). Their system supports component models from a range of different modelling tools, in addition to FMI support.…”
Section: Related Workmentioning
confidence: 99%
“…After the introduction of FMI, several authors have shown how to use it in modular simulations. A recent example is Neema et al (2014), who used FMI for component models which where integrated using HighLevel Architecture (HLA). Their system supports component models from a range of different modelling tools, in addition to FMI support.…”
Section: Related Workmentioning
confidence: 99%
“…A promising approach was suggested by Ptolemy II project [10] with a rigorous actor-based framework for handling heterogeneity of models by hierarchical composition of different MoCCs (Models of Computation and Communications) [11]. Another research direction is focused onintegration of Simulink, Modelica and other modeling tools with Systems Seattle, July [13][14][15][16]2015 Engineering languages like SysML. Authors of [12] developed a UML profile and a complementary software that enables referencing Simulink models from SysML model.…”
Section: Related Workmentioning
confidence: 99%
“…Simulations are also widely used to evaluate complex systems, such as cyber-physical systems, by cosimulating behaviors of component systems/networks in a hierarchical High-Level Architecture (HLA) [25], [26]. Eventdriven simulators, such as NS2/NS3, OPNET and OMNET++, are developed for such purposes [28], [27].…”
Section: Introductionmentioning
confidence: 99%